Investigating notification presentation and interaction in augmented reality - Plabst, Lucas, author; Ortega, Francisco, advisor; Niebling, Florian, advisor; Arefin, Mohammed, committee member; Soto, Hortensia, committee member; Trinkenreich, Bianca, committee member (Colorado State University. Libraries, 2025)
This thesis explores optimal notification display and interaction techniques in augmented reality (AR) environments. Through six experiments, we examined notification positioning, modality, interaction methods, real-world smartglasses usage, and task resumption strategies for interruptions. Our findings provide insights into designing effective AR notification systems while balancing usability and intrusiveness. First, we investigated notification placement in 3D AR environments using a memory task, finding that bottom-center positioning in the field-of-view (FOV) is ideal for general tasks, while world-anchored notifications suit stationary tasks. Next, we explored notification location and modality in a simulated cooking task, revealing that multimodal notifications placed on task-relevant objects improve user performance. We further analyzed notification interaction methods, determining that a body-attached notification list is the preferred option for users and that touch interaction outperforms gaze and voice input. In a follow-up study, we assessed multimodal interaction, noting its potential compared to unimodal interaction, but also highlighting reliability concerns due to modality fusion challenges. Beyond controlled environments, we conducted a five-day field study with smartglasses, demonstrating the benefits of hands-free, real-time notifications but also highlighting barriers such as social acceptability and attentional costs. Lastly, we designed an AR-based task resumption aid, showing that visual cues at the point of interruption significantly reduce resumption lag, potentially mitigating the disruptive effects of notifications. As AR devices become more pervasive, notification systems must be thoughtfully designed to balance intrusiveness with utility. This research informs future AR notification strategies, emphasizing adaptability to dynamic real-world contexts.
Also includes abstract in German.
Keywords: notifications; user experience; augmented reality; user research; usability